2021
DOI: 10.1080/1369183x.2021.1978285
|View full text |Cite
|
Sign up to set email alerts
|

Re-visiting the ‘black box’ of migration: state-intermediary co-production of regulatory spaces of labour migration

Abstract: It is now widely held that a variety of intermediary actors, including recruitment and staffing agencies, multinational corporations and local brokers, shape labour migration. This paper argues that in order to better understand the global circulation of labour it is necessary to explore the involvement of these actors in the production of the regulatory spaces through which migrant labour is brokered. Indeed, migration intermediaries do not only navigate borders on behalf of their migrant clients. Nor is 'the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…From this in-between position they sometimes influence immigration policy and practice directly, for example by engaging in dialogue with state actors (Hedberg and Olofsson, forthcoming), or contesting decisions by immigration authorities or the immigration system at large (Khan, 2019). Their influence can equally be indirect, for example when the exploitative practices of certain intermediary actors prompt stricter regulations (Axelsson et al., 2021). Similarly, scalar readings of migration governance tend to emphasise how certain responsibilities for immigration control have been placed on actors beyond the state.…”
Section: Introductionmentioning
confidence: 99%
“…From this in-between position they sometimes influence immigration policy and practice directly, for example by engaging in dialogue with state actors (Hedberg and Olofsson, forthcoming), or contesting decisions by immigration authorities or the immigration system at large (Khan, 2019). Their influence can equally be indirect, for example when the exploitative practices of certain intermediary actors prompt stricter regulations (Axelsson et al., 2021). Similarly, scalar readings of migration governance tend to emphasise how certain responsibilities for immigration control have been placed on actors beyond the state.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the evidence presented, we need to be careful not to think of migration policymaking as shaped by political elites or business interests but to see both political elites and business interests as intimately entangled within and co-producing labour migration policy (see also Axelsson et al, 2021;Hedberg and Olofsson, 2022). Pressure from employers for continued low-wage labour migration after Brexit has been strong and, in the food production sector at least, it has correlated with policy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the UK, Menz (2011: 12) has observed that: 'European employer associations have rediscovered an appetite for labour migrants', and that 'governments are heeding calls for more liberalised approaches to managing economic migration'. Recent evidence from Sweden underlines this point, demonstrating very clearly how the regulatory spaces of labour migration are now being co-produced by both migration intermediaries (such as recruitment agencies and corporations) and state actors (Axelsson et al, 2021;Hedberg and Olofsson, 2022). Freeman's (1995) arguments, it appears, have gained relevance as the UK, among other developed states, has undergone a period of expansive immigration.…”
Section: Migration Policymaking and The 'Need' For Low-wage Foreign W...mentioning
confidence: 99%
See 2 more Smart Citations